2020
DOI: 10.1186/s12879-020-05146-9
|View full text |Cite
|
Sign up to set email alerts
|

What is the level of uptake of partner notification services in HIV testing in selected health facilities in Gatanga Sub County, Muranga County – Kenya; a retrospective study

Abstract: Background: Identification of people living with HIV is key in HIV prevention and control. Partner Notification service is a World Health Organization backed strategy of reaching out to sexual partners of people diagnosed with HIV for HIV testing. However, its adoption and success rate in Kenya remains unknown. Methods: A cross sectional facility based study was undertaken in five purposely selected health facilities in Gatanga Sub county, Muranga County, Kenya. A retrospective review of patient medical record… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…Index testing services were well-accepted during the first and second year, 97.4% and 99%, respectively, for the general population and resulted in an increase in the number of HIV-positive individuals identified. High levels of acceptance, ranging from 89% to 99%, have also been reported in other studies conducted in SSA [11,18,21,22]. The elicitation ratio and testing uptake also significantly improved over the evaluation period.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Index testing services were well-accepted during the first and second year, 97.4% and 99%, respectively, for the general population and resulted in an increase in the number of HIV-positive individuals identified. High levels of acceptance, ranging from 89% to 99%, have also been reported in other studies conducted in SSA [11,18,21,22]. The elicitation ratio and testing uptake also significantly improved over the evaluation period.…”
Section: Discussionsupporting
confidence: 77%
“…These populations may be reluctant to disclose information due to several factors, including stigma and discrimination. Most studies on index testing in Kenya have been conducted in a controlled environment or were restricted to only a few select facilities [13,[15][16][17][18]. To fill this gap, we present the implementation strategies of the index testing program in Nairobi county, Kenya, and assess outcomes and changes along the HIV index testing cascade during the first 2 years of implementation.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study in Kenya reported index testing acceptance rate of 89% and elicitation ratio of 1:1.3. 26 We observed that the four supportive strategies were particularly important to overcome key programmatic difficulties we faced during community HTS implementation, such as pervasive security challenges, distrust and suspicion whenever community testers were seen in communities, insufficient mentorship, low morale among field testers, and a culture of low data use to guide decisions among program implementers. Leveraging alternative healthcare outlets, such as traditional and spiritual healers, traditional birth attendants, pharmacists, and patent medical vendors, as well as involvement of community leaders and influencers, 27 helped to provide services safely in security-challenged areas.…”
Section: Discussionmentioning
confidence: 94%
“…A similar study in Kenya reported index testing acceptance rate of 89% and elicitation ratio of 1:1.3. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials and demonstration projects in sub-Saharan Africa show that APS is a safe, efficient, and effective strategy to reach individuals who have been exposed to HIV with testing and linkage to care. 7 - 12 A meta-analysis 13 reported that APS was associated with a 50% increase in HIV testing among partners compared with standard of care, with few adverse events. In Kenya, a cluster-randomised clinical trial 9 reported that APS provision resulted in higher partner HIV testing, identification of newly diagnosed HIV in partners, linkage to care, and first-time testers compared with passive referral.…”
Section: Introductionmentioning
confidence: 99%